The Linux Enterprise Cluster : build a highly available cluster with commodity hardware and free software - Kopper, Karl (No Starch Press, 2005)
The Linux Enterprise Cluster shows how to turn a number of inexpensive networked computers into one powerful server. Learn how to: build a high-availability server pair using Heartbeat, use the Linux Virtual Server load balancing software, configure a reliable printing system in a Linux cluster environment, and build a job scheduling system in Linux with no single point of failure. The CD includes the Linux kernel, ldirectord, Mon, Ganglia, OpenSSH, rsync, SystemImager, Heartbeat, and all figures and illustrations used in the book.